Status of youth in Mexico and drug trafficking. Binomial of the emergence of a subculture - et. al., Mijael Altamirano Santiago, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Analyze the current problems in Mexico around drug trafficking, since the co-optation of children and young people by organized crime groups has been perceived as one of the most worrying situations that affect society. Method. It raises the possibility of observing the object-subject of investigation based on the differential association theory and its implication in the drug trafficking subculture, since although this theory has not been created for the Mexican case, it houses an interesting application that can pay to a better understanding of the problem raised. Result / conclusions. Based on data obtained from different sources, including social and crime theoretical developments, the relatively recent nature of youth participation within the drug trafficking subculture in Mexico.